Effect of arsenic stress on 5-methylcytosine, photosynthetic parameters and nutrient content in arsenic hyperaccumulator Pteris cretica (L.) var. Albo-lineata - Zemanová, Veronika; Popov, Marek; Pavlíková, Daniela; Kotrba, Pavel; Hnilička, František; Česká, Jana; Pavlík, Milan (BMC plant biology, 2020)
BACKGROUND: Arsenic toxicity induces a range of metabolic responses in plants, including DNA methylation. The focus of this paper was on the relationship between As-induced stress and plant senescence in the hyperaccumulator Pteris cretica var. Albo-lineata (Pc-Al). We assume difference in physiological parameters and level of DNA methylation in young and old fronds as symptoms of As toxicity. RESULTS: The As accumulation of Pc-Al fronds, grown in pots of haplic chernozem contaminated with 100 mg As kg- 1 for 122 days, decreased with age. Content of As was higher in young than old fronds for variants with 100 mg As kg- 1 (2800 and 2000 mg As kg- 1 dry matter, respectively). The highest As content was determined in old fronds of Pc-Al grown in pots with 250 mg As kg- 1. The increase with age was confirmed for determined nutrients - Cu, Mg, Mn, S and Zn. A significant elevation of all analysed nutrients was showed in old fronds. Arsenic accumulation affected DNA methylation status in fronds, but content of 5-methylcytosine (5mC) decreased only in old fronds of Pc-Al (from 25 to 12%). Determined photosynthetic processes showed a decrease of fluorescence, photosynthetic rate and chlorophylls of As treatments in young and old fronds. Water potential was decreased by As in both fronds. Thinning of the sclerenchymatous inner cortex and a reduction in average tracheid metaxylem in the vascular cylinder was showed in roots of As treatment. Irrespective to fronds age, physiological parameters positively correlated with a 5mC while negatively with direct As toxicity. Opposite results were found for contents of Cu, Mg, Mn, S and Zn. CONCLUSIONS: The results of this paper point to changes in the metabolism of the hyperaccumulator plant Pc-Al, upon low and high exposure to As contamination. The significant impact of As on DNA methylation was found in old fronds. Irrespective to fronds age, significant correlations were confirmed for 5mC and As toxicity. Our analysis of the very low water potential values and lignification of cell walls in roots showed that transports of assimilated metabolites and water between roots and fronds were reduced. As was showed by our results, epigenetic changes could affect studied parameters of the As hyperaccumulator plant Pc-Al, especially in old fronds.
Keywords: listy rostlin; DNA demethylation; kořeny rostlin; Chlorophyll; Toxic element; arsen; Plant Roots; Epigenetic change; Plant Leaves; chlorofyl; Pteridaceae; metylace DNA; 5-Methylcytosine; Arsenic; Soil Pollutants; DNA Damage; fotosyntéza; Pteris; DNA Methylation; Photosynthesis; Long-term stress; 5-methylcytosin; poškození DNA; Nutrients; ekotoxikologie; látky znečišťující půdu; Ecotoxicology; živiny